Paleomagnetic ages of lateritic crusts in Amazonia - Horbe, Adriana Maria Coimbra (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
This work presents the first results about the dating of lateritic crusts in Amazonia using the paleomagnetism technique. For the study were selected samples from seven sites that represent the lateritic evolution on craton rocks and on Paleozoic sedimentary rocks in Amazonia. For six of these occurrences, the lateritic crusts could be correlated with the curve of the continental drift of South America for post-Cretaceous events. In this way, the oldest crusts developed on Prosperança and Nhamundá Formations (sedimentary rocks of Neoproterozoic and Lower Silurian, respectively) indicate ages between 70 and 80 Ma, while for the bauxite crusts of Miltonia and Trombetas (Alter do Chão and Itapecuru Formations, both Upper Cretaceous) and the most recent and exclusively ferruginous crusts of Manaus (Alter do Chão Formation) are suggested, respectively, ages between 28-50 Ma and 10 Ma. Such ages, which are compatible with the geological evolution of the laterization in the Amazon, allow to identify, with greater precision, the chronology of the formation of the bauxite and ferruginous crusts and provided new subsidies to delimit areas of exposure and the correlation with the tectonic evolution of the region during the Cenozoic.